A NEW ALGORITHM FOR EXTRACTION OF CONTINUOUS CHANNEL NETWORKS WITHOUT PROBLEMATIC PARALLELS FROM HYDROLOGICALLY CORRECTED DEMS - Gulgen, Fatih; Gokgoz, Turkay (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2010)
One of the most popular flow-routing approaches to the extraction of channel networks from DEMs is the D8 approach. Several algorithms based on this method have been developed so far, but none provides a satisfactory solution to the problem of parallel lines. In this study, a new algorithm named DRainage Axis Way (DRAW) is developed. It has seven core routines, and three of them are similar to the Profile Recognition and Polygon Breaking Algorithm (PPA). It is a segment based computation system, but it uses flow accumulation data as well. It works on hydrologically corrected DEMs. In DRAW, the flow accumulation threshold value is determined automatically with respect to the occurrence of parallel lines depending on terrain forms. For experimental testing, two hydrologically corrected 5 m DEMs were used. Four sets of channel networks were extracted from the DEMs by using PPA, D8 with two different stream thresholds, and DRAW. For comparison, an existing channel network on a map with a scale of 1: 5,000 was utilized as a ground-truth.
Keywords: DRAW; Accumulation; D8; PPA; DIGITAL ELEVATION MODELS; DRAINAGE NETWORKS; AREAS; RECOGNITION; CONTOURS; LINES; FLOW; Geochemistry & Geophysics; Remote Sensing